Factors Influencing Customer Satisfaction at Gwalk Surabaya Es Teh Indonesia Outlet - Alifah Rafidah Putri; Gyska Indah Harya; Ida Syamsu Roidah (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
Customer complaints regarding service occur when purchasing beverage products at the Gwalk Es Teh Indonesia Outlet. Several factors influence consumer satisfaction. The research examines how customer satisfaction at the Gwalk Es Teh Indonesia Outlet is impacted by location, pricing, promotion, brand image, and service quality. This research was conducted at the Gwalk Citraland Es Teh Indonesia Outlet, Lakarsantri District, Surabaya City. This research use 100 respondents. The research method used is Structural Equation Model Partial Least Square (SEM PLS) analysis with the Warp PLS version 8.0 application. There were 100 responders in this research. The Warp PLS version 8.0 application uses the Structural Equation Model Partial Least Square (SEM PLS) analytic study approach. Primary and secondary data are the types of data collected. The study's findings indicate that the variables that significantly impact consumer satisfaction are brand image (p-value = 0.003), price (p-value <0.001), location (p-value <0.014), and service quality (p-value <0.001), provided that the p-value is less than 0.05. However, because the promotion variable has a p-value of more than 0.05, it does not match the standards due to its high p-value of 0.189. The study concludes that promotions at the Gwalk Es Teh Indonesia Outlet have no effect on customer happiness, but brand image, pricing, location, and service quality do. Based on the study's findings, the Gwalk Es Teh Indonesia Outlet can continue to sell its items at the same price and location while maintaining its brand image by responding to client demands and giving them faster, more accurate service to boost customer satisfaction.